G385 RATNO – Reducing Antibiotic Tolerance using Nitric Oxide in Cystic Fibrosis: report of a proof of concept clinical trial. (7th April 2014) - Cathie, K; Howlin, R; Carroll, M; Clarke, S; Connett, G; Cornelius, V; Daniels, T; Duignan, C; Hall-Stoodley, L; Jefferies, J; Kelso, M; Kjelleberg, S; et al.
Abstract : Aims: To investigate whether low dose Nitric Oxide (NO) enhances antibiotic therapy through disruption of Pseudomonas aeruginosa (PA) bacteria in biofilms in patients with Cystic Fibrosis (CF). Background: Bacterial biofilms present a major challenge due to their antimicrobial tolerance. In CF, chronic PA infection cannot be eradicated with conventional antibiotics, leading to increased hospitalisation, intravenous (IV) antibiotic use, more rapid decline in lung function and reduced survival. PA biofilms are dispersed in ex vivo samples by nanomolar, non-toxic concentrations of NO. Biofilm dispersal is signalled by NO via cyclic-di-GMP leading to increased susceptibility of PA to tobramycin and ceftazidime. Method: We carried out a participant blind, placebo controlled, randomised trial to investigate whether low dose NO enhances antibiotic therapy through disruption of PA bacteria in biofilms in patients with CF (EudraCT 2010–023529–39). 12 patients received 7 days of NO gas or placebo (air) via nasal cannula for 8 h alongside standard IV antibiotics during a pulmonary exacerbation. Primary outcome was microbiological quantification of PA measured using Fluorescent In Situ Hybridisation (FISH), Quantitative-Polymerase Chain Reaction (Q-PCR) and Colony Forming Units (CFUs). Clinical parameters including lung function and quality of life were secondary outcome measures to monitor safety. Result: Generalised estimating equation analyses of FISH data demonstrated significant reduction in PA biofilm from day 0 to 7 [mean Ln difference between groups 3.49 (95% CI: 0.32, 6.67; p = 0.031) for > 20 bacterial cell aggregates and 4.47 (95% CI: 0.04, 8.98; p = 0.052) for biofilm volume]. CFU and Q-PCR analyses were also consistent with the primary hypothesis (data not shown). The treatment group showed some benefit in FEV1 and FVC during the period of treatment. Mean percentage predicted FEV1 increased by 15.6% (95% CI –5.76–36.96) in the treatment group, compared to 6.67% (95% CI: 1.99–11.3) for placebo. Mean percentage predicted FVC increased by 16% (95% CI –8.94–40.942) in the treatment group and 4.8% (95% CI –2.24–11.90) in the placebo group. Conclusion: These data show preliminary evidence of benefit using low dose NO as adjunctive therapy with ceftazidime and tobramycin during a 7 day treatment period. Novel targeted NO-donor antimicrobial therapies are being investigated that may enable long term biofilm control and the reduction of PA-related morbidity.